INDUSTRIAL-ECONOMIC ZONE SOCIAL AUTHORITY GUARANTEE - Ashirov Valijon Ilkhomovich Navoi (Antis Publisher, 2024)
In this article, scientific information about economic zones, which are the drivers of the economy of developed countries in the world experience, is presented. Introduction of foreign investments in industrial zones through economic reforms implemented in Navoi Uzbekistan, application of foreign projects, as well as Navoi free industrial zone, one of the first industrial zones in the republic, and its establishment today. Free economic zones in Uzbekistan have been highlighted.